Isolation and cytotoxicity of triterpenes from the roots of Phyllanthus pulcher Wall. ex Müll. Arg. (Euphorbiaceae). - Bagalkotkar, Gururaj; Tang, Seng Chuan; Khalivulla, Shaik Ibrahim; Hamzah, Ahmad Sazali; Shaari, Khozirah; Lajis, Md. Nordin; Saad, Mohammad Said; Stanslas, Johnson (Academic Journals, 2011)
The dried powdered roots of Phyllanthus pulcher Wall. ex Müll. Arg. (Euphorbiaceae), were sequentially extracted with dichloromethane (DCM), ethyl acetate (EtOAc) and methanol (MeOH). The extracts were tested for cytotoxic activity against three human cancer cell lines: MCF-7 (breast), NCI-H460 (lung) and DU-145 (prostate). The DCM extract exhibited the strongest cytotoxic activity compared with EtOAc and MeOH extracts. Hence from the DCM extract, five pentacyclic triterpenes, 3α-acetoxyl-25-hydroxyolean-12-en-28-oic acid (1), glochidone (2), 12(13)-dehydro-3α-acetoxyolean-28-oic acid (3), lupanyl acetate (4) and glochidonol (5) were isolated and identified by spectroscopic analyses (1H NMR, 13C NMR, FT-IR, UV, DEPT, HMQC, HMBC and HREIMS). This is the first report on the isolation of 4 from a natural source, whereas 1 and 3 have already been isolated from the families Hamamelidaceae and Compositae (Asteraceae), respectively. However this is the first study reporting the presence of 1 and 3 in the Euphorbiaceae family. The isolated tritepenes 1-5 were tested against the three human tumour cell lines as stated above. Only compounds 1 and 5 exhibited cytotoxic activity, 5 being most potent with IC50 values ranging 7.5–13.4 µg/mL (17.1–30.5 µM).